Risk profiles of treatment noncompletion for inpatients and outpatients undergoing alcohol disorder rehabilitation treatment - Preuss UW; Zimmermann J; Schultz G; Watzke A; Schmidt P; Loehnert B; Soyka M (Dove Medical Press, 2012)
Ulrich W Preuss,1 Jörg Zimmermann,2,3 Gabriele Schultz,2 Anna Watzke,2 Peggy Schmidt,4 Bärbel Löhnert,5 Michael Soyka2,61Department of Psychiatry, Psychotherapy and Psychosomatics, University of Halle-Wittenberg, Halle, Germany; 2Ev Krankenhaus Bethanien GmbH, Fachklinik Gristower Wiek, Johanna-Odebrecht-Stiftung, Germany; 3Karl-Jaspers-Klinik, Fachkrankenhaus für Psychiatrie und Psychotherapie, Psychiatrieverbund Oldenburger Land, Germany; 4Department of Psychiatry, Ludwig-Maximilians-Universität Munich, Germany; 5Klientenzentrierte Problemberatung, Dachau/Munich, Germany; 6Privatklinik Meiringen, Meiringen, Switzerland Background: Rehabilitation treatment noncompletion is considered a risk factor for long term relapse in alcohol-dependent individuals. The aim of this analysis of in- and outpatients in alcohol dependence rehabilitation in Germany is to identify social, mental, and somatic risk profiles for treatment noncompletion.Methods: A total of 92 individuals from an outpatient program and 303 individuals from two inpatient rehabilitation treatment units in three different locations in Germany were recruited and assessed with a structured interview and several measures of psychopathology (personality disorders, anxiety, depression, and impulsivity) at treatment admission, with termination at 12 months follow-up. Participants were subdivided into treatment completers and noncompleters for any reason.Results: A total of 10.2% of inpatients and 16.1% of outpatients did not complete treatment. Compared with treatment completers, noncompleters had a significantly lower rate of continuous abstinence at 1-year follow-up, more recent alcohol consumption before admission, and a higher rate of borderline personality disorders. Among inpatients, an elevated rate of lifetime mental disorders, depression, and suicide attempts was found among treatment noncompleters; among outpatients, treatment noncompleters were more often than completers to be married but live separated.Conclusion: Rates of treatment noncompletion in inpatient and outpatient rehabilitation programs correspond to results from previous research. Noncompletion is a significant correlate of relapse 1 year after treatment, and noncompleters show an elevated level of psychopathology. These findings may help rehabilitation treatment facilities to tailor specific therapies for these individuals to reduce risk for treatment noncompletion.Keywords: alcohol dependence, rehabilitation treatment, noncompletion, inpatient, outpatient